Numerical investigation of the effect of an air layer on the melting process of phase change materials - Abbas Fadhil Khalaf; Farhan Lafta Rashid; Mudhar A. Al-Obaidi; Arman Ameen; Hayder I. Mohammed (Materials for Renewable and Sustainable Energy)
Abstract Designing more effective thermal energy storage devices can result from understanding how air layers impact the melting process. The total efficiency of these systems can be improved by optimizing the melting process of the phase change materials (PCMs), which are utilised to store and release thermal energy. The current study utilises an analysis to evaluate how an air layer would affect melting of the PCM. The enthalpy-porosity combination based ANSYS/FLUENT 16 software is specifically used to accomplish this study, considering the paraffin wax (RT42) as the PCM. The study reveal that the presence of an air layer would impact the dissolution process. This result is assured an increase of melting time of PCM by 125% as a result to having an air layer of 5 cm thickness compared to a cell without an air layer. Furthermore, an increase of the layer thickness beyond 5 cm has a progressive effect on the melting time of PCM. One important component that affects the melting process is the existence of an air layer above the cell. Greater heat transfer resistance from thicker air layers prolongs the time needed to finish melting. The efficient heat transmission of PCM is shown to be reduced when there is an air layer above the cell. The melting process gradually slows down as the air layer thickness rises, which reflects the decreased heat transmission. These results highlight how crucial it is to take the environment into account while creating PCM-filled energy storage cells.